On the diversity of microfossils in the Bazhenov Horizon of Western Siberia (Late Jurassic–Early Cretaceous) - E. O. Amon; V. S. Vishnevskaya; Yu. A. Gatovsky; E. A. Zhegallo (Georesursy, 2024)
Paleontological remains from the Bazhenovo Horizon of Western Siberia (Tithonian–Berriasian) are represented by macro- and microfossils. The Horizon had a marine genesis and the basis of ecosystem of this paleobasin composed of pelagic organisms-producers (phytoplankton: prasinophytes, coccolithophorids, dinoflagellates, as well as brown algae) and consumers (zooplankton: radiolarians, invertebrate larvae, crustaceans; and nekton: pelagic bony fish, ammonites, belemnites, paleosquids-teutids and marine dinosaurs; and, in addition, benthic bivalves, foraminifera, and ostracods). Among microfossils, radiolarians are the leading importance, phytoplankton (dinoflagellates, coccolithophorids) and microbenthos (foraminifera, sponge spicules) are less common. Radiolarians, dinoflagellates, coccolithophorids, and foraminifera are used for biostratigraphic subdividing of sections and their correlation, and, in addition, together with sponge spicules, for reconstruction the paleoenvironments. In literature, a several paper indicated the presence of other siliceous microfossils in paleobiota of the Bazhenovo paleosea – diatoms, silicoflagellates, and acantharians. The article summarized data on radiolaria, coccolithophorids, dinophyta and critically reviewed reports of other microobjects. It is shown that the information about diatoms, silicoflagellates and acantharians from Bazhenovo Horizon and Bazhenovo Formation is probably unreliable.